Growth Dynamics of Lithuanian Blackface Lambs: Role of Crossbreeding with German Blackheaded Mutton Rams, Sex and Seasonality - Rūta Šveistienė; Violeta Razmaitė (Agriculture)
Crossbreeding is widely used to improve livestock performance, combining favorable breed traits through additive effects while maintaining genetic diversity. This approach enhances sheep farming economic sustainability to improve reproduction timing and prolificacy. Optimizing litter size is crucial for maximizing lamb production under diverse conditions, and breeding programs worldwide focus on both within-breed selection and crossbreeding strategies. This study aimed to evaluate the effects of the controlled introgression of German Blackheaded Mutton (GBM) rams on ewe prolificacy and lamb growth while preserving breed structure and integrity. The study examined the effects of genotype, litter size, season, and sex on lamb birth weight and growth. Genotype significantly influenced birth weight (p < 0.01), with crossbreeds containing 6.25% GBM having the highest weights, though higher GBM proportions had no additional benefit. Crossbred lambs outperformed purebred Lithuanian Blackface (LBF) lambs at all measured ages. Litter size significantly affected birth weight (p < 0.001) and growth, with larger litters leading to lighter lambs. Seasonal effects were notable only at three months, with winter-born lambs weighing 2.45 kg more than spring-born lambs (p < 0.010). Most lambings occurred in winter (71.4%). Male lambs were heavier than females at eight months (3.45 kg difference, p < 0.010). Genotype–season interactions influenced weights at several ages, with winter-born purebred LBFs and certain crossbreeds generally outperforming their spring-born counterparts. Lambs from single-lamb litters were consistently heavier, especially in winter and summer. These findings emphasize the interplay of genetics, season, and litter size on lamb growth.